Pengaruh Perceived Usefulness, Trust dan Perceived Risk Terhadap Purchase Intention Pengguna Shopee - Viorendra Anggi Irvania (Akmenika: Jurnal Akuntansi dan Manajemen, 2022)
This study aims to examine the effect of perceived usefulness, trust, and perceived risk on purchasing intention. This research was conducted on 100 respondents of Shopee users in MAN 1 Gunungkidul students. The data was collected by distributing questionnaires using a 1-5 point Likert scale to measure 12 indicators. The analysis technique used in this research is descriptive analysis. The results of this study indicate: 1) Perceived Usefulness, Trust and Perceived Risk have a positive effect on Purchase Intention 2) Perceived Usefulness has a positive effect on Purchase Intention 3) Trust has a positive effect on Purchase Intention 4) Perceived Risk has a positive effect on Purchase Intention.Keywords : Perceived Usefulness, Trust, Perceived Risk, Purchase Intention